DIVERSITY OF PLASMODIAL MYXOMYCETES FROM ANDA ISLAND, PANGASINAN, PHILIPPINES - Thomas Edison dela Cruz (SEAMEO BIOTROP, 2013)
The unique life cycle and fascinating fruiting bodies of myxomycetes make them ideal model organisms for the study of cellular differentiation. Our research study then focuses on the diversity and abundance of myxomycetes found in Anda Island, Pangasinan in Northern Philippines. A total of 180 moist chambers were prepared from ground leaf litter and twigs collected from a 15 m2 quadrat within the study site. Twenty four species of myxomycetes belonging to 11 genera were collected and identified from the moist chambers: Arcyria (2), Collaria (1), Comatricha (1), Craterium (2), Diachea (1), Diderma (2), Didymium (1), Elaeomyxa (1), Perichaena (1), Physarum (11), and Stemonitis (1). Of all moist chambers, 55% yielded myxomycetes. Ground leaf litter (29%) yielded more myxomycetes than twigs (26%). Among the collected species, one for each of the genera Arcyria, Craterium, Diderma, and Physarum were recorded to be abundant. Interestingly, three species of myxomycetes are new records for the Philippines: Craterium microcarpum, Physarum decipiens and Elaeomyxa miyazakiensis. This is the first report of myxomycetes in Anda Island, Pangasinan, Philippines.